Social capital, network effects and savings in rural Vietnam - Carol Newman; Finn Tarp; Katleen Van Den Broeck (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Information failures are a major barrier to formal financial saving in low income countries. Households in rural communities often lack the information necessary to set up formal deposit accounts or are uncertain about the returns to saving formally. In this paper, we explore the extent to which social networks in rural Vietnam can play a role in increasing formal savings where knowledge gaps exist. Networks are defined as active membership of women's unions and the quality of networks is measured by the level of formal savings observed among group members. We find that membership of high quality networks leads to higher levels of saving in formal financial institutions and to higher levels of saving for productive investments as compared with other precautionary or lifecycle motives. Our results suggest that transmitting financial information through formal networks could be effective in increasing formal savings at grassroots level. We also conclude that ensuring information disseminated by networks is both accurate and desirable as well as important given that behavioural effects are also found in low-quality networks.
Keywords: D14; D71; D83; O12; 330; household savings; social capital; information failure; women's unions; Vietnam; Social Capital; Soziales Netzwerk; Sparen; Asymmetrische Information; Landbevölkerung; Vietnam